2021
DOI: 10.1002/adhm.202101349
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell Membrane‐Coated Nanoparticles: Recent Development and Medical Applications

Abstract: White blood cells (WBCs) are immune cells that play essential roles in critical diseases including cancers, infections, and inflammatory disorders. Their dynamic and diverse functions have inspired the development of WBC membrane-coated nanoparticles (denoted "WBC-NPs"), which are formed by fusing the plasma membranes of WBCs, such as macrophages, neutrophils, T cells, and natural killer cells, onto synthetic nanoparticle cores. Inheriting the entire source cell antigens, WBC-NPs act as source cell decoys and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 100 publications
0
65
0
Order By: Relevance
“…Immune cell membrane‐coating nanotechnology is an emergent and nature‐inspired approach that harnesses good biocompatibility, long blood circulation time, and enhanced specificity of immune cells to migrate to inflamed tissues and tumors. [ 23,28 ] This strategy overcomes the shortcomings of nanomaterials, improves the delivery of therapeutic agents and diagnostic compounds to sites of interest. Consequently, the strategy may enhance the clinical results achieved with NP‐based systems.…”
Section: Immune Cell‐membrane Coating Nanotechnology: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Immune cell membrane‐coating nanotechnology is an emergent and nature‐inspired approach that harnesses good biocompatibility, long blood circulation time, and enhanced specificity of immune cells to migrate to inflamed tissues and tumors. [ 23,28 ] This strategy overcomes the shortcomings of nanomaterials, improves the delivery of therapeutic agents and diagnostic compounds to sites of interest. Consequently, the strategy may enhance the clinical results achieved with NP‐based systems.…”
Section: Immune Cell‐membrane Coating Nanotechnology: An Overviewmentioning
confidence: 99%
“…[41,42] Using immune cell membranes to functionalize the NPs via top-down approaches has emerged as a versatile and very promi sing strategy to prolong the blood circulation time in vivo, and achieve a more precise and efficient accumulation of these nanosystems in inflamed, infectious, and neoplastic tissues. [23,28] However, despite these advantages, producing macrophages on a clinical scale suitable for universal use is a demanding task, due to immunological and safety concerns arising from the presence of proteins involved in triggering immune responses on the cell membranes (e.g., MHC molecules). Therefore, due to the high risk of immune rejection when using allogeneic cells, human macrophages should be genetically modified after being extracted to reduce undesirable side effects.…”
Section: Challenges In Clinical Translation and Future Prospectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, although nanomedicine has made great progress in cancer diagnosis and treatment, a variety of biological barriers such as low targeting and immune cell removal are still a challenge in vivo [ 39 , 40 ] . More and more studies have shown that nanoparticles encapsulated with natural biological cell membranes can have the advantages of homologous cells, which has attracted more and more attention [ 22 , 23 , 41 , 42 ]. Cancer cells may escape from the immune system due to some antigens on the surface of the cancer cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these challenges and reduce the gap between nanoplatform and clinical application, the natural biological cell membranes coated nanoparticles that not only has the physical and chemical properties of nanomaterials, but also possesses the advantages of homologous cells have attracted more and more attention [ [21] , [22] , [23] , [24] ]. Studies have showed that cancer cells have immune escape ability due to cancer associated antigens and immune adjuvants on the surface of the membrane [ [25] , [26] , [27] ], and homologous targeting ability [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%